Providing manualized individual trauma-focused CBT to unaccompanied refugee minors with uncertain residence status: a pilot study - Johanna Unterhitzenberger; Svenja Wintersohl; Margret Lang; Julia König; Rita Rosner (BMC, 2019)
Abstract Background Unaccompanied refugee minors (URMs) seeking asylum show high rates of posttraumatic stress disorder (PTSD), depression and anxiety. In addition, they experience post-migration stressors like an uncertain residence status. Therefore, psychotherapeutic interventions for URMs are urgently needed but have scarcely been investigated up to now. This study aimed to examine manualized individual trauma-focused cognitive behavioural therapy (TF-CBT) for URMs with PTSD involving their professional caregivers (i.e. social workers in child and adolescent welfare facilities). Methods We conducted an uncontrolled pilot study with three follow-up assessments (post-intervention, 6 weeks, and 6 months). Participants who met the PTSD diagnostic criteria were treated in a university psychotherapeutic outpatient clinic in Germany with a mean of 15 sessions of TF-CBT. All participants (n = 26) were male UM (Mage = 17.1, SD = 1.0), predominately from Afghanistan (n = 19, 73.1%) and did not have a residence permit. The sample was severely traumatized according to the number of traumatic event types reported (M = 11.3, SD = 2.8). The primary outcome was PTSD measured with the Child and Adolescent Trauma Screen (CATS) and the Diagnostic Interview for Mental Disorders in Childhood and Adolescence (Kinder-DIPS). Secondary outcomes were depression, behavioural and somatic symptoms. All but the somatic symptoms were assessed in both self-report and proxy report. Results At post-intervention the completer sample (n = 19) showed significantly decreased PTSD symptoms, F(1, 18) = 11.41, p = .003, with a large effect size (d = 1.08). Improvements remained stable after 6 weeks and 6 months. In addition to PTSD symptoms, their caregivers reported significantly decreased depressive and behavioural symptoms in participants. According to the clinical interview, 84% of PTSD cases recovered after TF-CBT treatment. After 6 months, youths whose asylum request had been rejected showed increased PTSD symptoms according to individual trajectories in the Kinder-DIPS. The effect was, however, non-significant. Conclusions Intervention studies are feasible with URMs. This pilot study presents preliminary evidence for the efficacy of an evidence-based intervention like TF-CBT in reducing PTSD symptoms in URMs. Stressors related to asylum proceedings after the end of therapy have the potential to negatively influence psychotherapy outcomes.